Nutritional status of orange tree 'Pêra Rio' variety after Huanglongbing disease infection, leaf spray fertilization and application of resistance-inducing bioinductors - Ferraz, Rener Luciano de Souza; Barbosa, Marcelo de Andrade [UNESP]; Viégas, Pedro Roberto Almeida; Costa, Patrícia da Silva; Melo, Alberto Soares de; Magalhães, Ivomberg Dourado; Neto, José Dantas; Medeiros, Aldair de Souza (Southern Cross Publishing, 2017)
Citrus industry is widespread in the world. The Huanglongbing is an important disease of citrus species and has been spread around the world. This research analyzed the nutritional status of tree 'Pêra Rio' variety infected with Candidatus Liberibacter spp., under leaf nutrients spray and bioinductors of resistance. The experiment was carried out from September 2013 to June 2014, in a citrus commercial orchard located in the city of Ibitinga (SP). A completely randomized design was used in a factorial 3 × 4 × 6, consisting of three plants status (healthy, infected with asymptomatic HLB, and symptomatic HLB), four rates of spray solutions (0, 2, 4 and 6 L ha-1), six application stages (A1, A2, A3, A4, A5, and A6 with intervals of 45 days between each stage) and four replications. Macro and micronutrients leaf levels were quantified. Data were submitted to exploratory factor analysis with multivariate statistics. Three factors were extracted from the variables, namely, Factor 1 formed by variables S, Cu, Fe, and Zn; Factor 2 by N, K and B, and Factor 3 by Ca, Mg, and Mn. 'Pêra Rio' plants nutritional status was destabilized with the infection of Candidatus Liberibacter spp. Progressive treatment with leaf fertilization and resistance bioinductors temporarily re-established nutritional standards of plants affected by Huanglongbing but did not promote stability of the plants nutritional status.
Keywords: Citrus sinensis; Elicitors; Ex-greening; Leaf nutrition